1994
DOI: 10.1523/jneurosci.14-10-05903.1994
|View full text |Cite
|
Sign up to set email alerts
|

Mu- and kappa-opioid receptors selectively reduce the same transient components of high-threshold calcium current in rat dorsal root ganglion sensory neurons

Abstract: Whole-cell patch-clamp recordings were used to examine the regulation of voltage-dependent calcium channels by mu- and kappa-opioid receptors in acutely isolated rat dorsal root ganglion (DRG) sensory neurons. Agonists selective for either mu- (Tyr-Pro-NMePhe-D-Pro-NH2, PLO17) or kappa-opioid receptors (dynorphin A, U69,593) inhibited high-threshold calcium currents in a reversible and naloxone-sensitive manner, whereas administration of D-Pen2,5-enkephalin, a delta-selective agonist, was without effect. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 38 publications
9
89
0
1
Order By: Relevance
“…Somatic recordings obtained from rat peripheral sensory (Schroeder et al, 1991;Moises et al, 1994;Rusin and Moises, 1995) and nucleus tractus solitarius neurons (Rhim and Miller, 1994) have identified several high-threshold Ca 2ϩ channels that are modulated by opioid receptors. In these neurons, -opioids, and -selective agonists to a lesser extent, inhibit Ca 2ϩ current contributed by GVIA-sensitive N-type and pharmacologically distinct P-and Q-type channels but spare L-and T-type currents, thereby regulating the principal Ca 2ϩ channel types involved in exocytosis at central synapses and peripheral sites of release (Luebke et al, 1993;Takahashi and Momiyama, 1993;Wheeler et al, 1994;Dunlap et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Somatic recordings obtained from rat peripheral sensory (Schroeder et al, 1991;Moises et al, 1994;Rusin and Moises, 1995) and nucleus tractus solitarius neurons (Rhim and Miller, 1994) have identified several high-threshold Ca 2ϩ channels that are modulated by opioid receptors. In these neurons, -opioids, and -selective agonists to a lesser extent, inhibit Ca 2ϩ current contributed by GVIA-sensitive N-type and pharmacologically distinct P-and Q-type channels but spare L-and T-type currents, thereby regulating the principal Ca 2ϩ channel types involved in exocytosis at central synapses and peripheral sites of release (Luebke et al, 1993;Takahashi and Momiyama, 1993;Wheeler et al, 1994;Dunlap et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Although it remains unclear how the presynaptic inhibitory effects of opioids are manifested, measurements from neuronal somata suggest that the depression of release may result from reductions in Ca 2ϩ influx through voltage-dependent Ca 2ϩ channels (North, 1993). Activation of -, ␦-, or -opioid receptors has been shown to inhibit somatic N-and P/Q-type Ca 2ϩ currents in several types of neurons (Schroeder et al, 1991;Moises et al, 1994;Rhim and Miller, 1994;Rusin and Moises, 1995) and clonal cells (Seward et al, 1991;Taussig et al, 1992). These same channel types have been implicated to play a pivotal role in mediating Ca 2ϩ influx that triggers depolarization-evoked neurotransmitter release from nerve endings in the periphery (Kongsamut et al, 1989;Toth et al, 1993) and CNS (Takahashi and Momiyama, 1993;Turner et al, 1993;Wheeler et al, 1994).…”
Section: Abstract: -Opioid Receptor; Ca 2ϩ Currents; Membrane Capacimentioning
confidence: 99%
“…The μ-, δ-, κ-, and ORL1 opioid receptor agonists inhibit neuronal activity through (1) inhibition of VGCCs in the DRG neurons (Moises et al, 1994a;Acosta and Lopez, 1999;Beedle et al, 2004;Wu et al, 2004), and (2) suppression of neuronal excitability through activation of GIRK channels in the postsynaptic neurons in the spinal cord (Schneider et al, 1998;Marker et al, 2006).…”
Section: Effect Of Opioid Receptor Agonists On Ion Channelsmentioning
confidence: 99%
“…Activation of μ-, δ-, κ-, and ORL1-opioid receptors inhibits VGCCs in dissociated DRG neurons (Moises et al, 1994a;Moises et al, 1994b;Acosta and Lopez, 1999;Beedle et al, 2004). For example, both morphine and DAMGO have been demonstrated to selectively inhibit N-type and P/Q-type Ca 2+ channels in DRG neurons (Schroeder et al, 1991;Schroeder and McCleskey, 1993;Wu et al, 2004).…”
Section: Effect Of Opioid Receptor Agonists On Ion Channelsmentioning
confidence: 99%
“…A number of studies have found that dynorphin can inhibit both N-type (Werz and Macdonald, 1984;Gross and Macdonald, 1987;Moises et al, 1994) and L-type (Moises et al, 1994) Ca 2ϩ channels. Our studies show that mossy fiber synaptic transmission is mediated by N-and P-type Ca 2ϩ channels (Castillo et al, 1994b).…”
Section: Abstract: Dynorphin; Receptors; Calcium Channels; Hippocampmentioning
confidence: 99%